2016
DOI: 10.1155/2016/1910292
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Stigma and Knowledge among Vietnamese in Ho Chi Minh City and Chicago

Abstract: Stigma regarding viral hepatitis and liver disease has psychological and social consequences including causing negative self-image, disrupting relationships, and providing a barrier to prevention, testing, and treatment. The aim of this study was to characterize and compare HBV knowledge and stigma in Vietnamese in Ho Chi Minh City and Chicago and to begin to evaluate the cultural context of HBV stigma. Methods. A written survey including knowledge questions and a validated HBV stigma questionnaire was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 17 publications
11
51
1
Order By: Relevance
“…In contrast, in the USA, several studies investigated the knowledge of Asian minorities about HBV. It was found that the knowledge of recruited subject was low about the means of transmission of HBV (19). In agreement of this, 90% of subjects involved in our study claimed that they do not know about the mode of transmission of HBV.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, in the USA, several studies investigated the knowledge of Asian minorities about HBV. It was found that the knowledge of recruited subject was low about the means of transmission of HBV (19). In agreement of this, 90% of subjects involved in our study claimed that they do not know about the mode of transmission of HBV.…”
Section: Discussionsupporting
confidence: 85%
“…One explanation could be because approximately half of the women surveyed believed that HBV can be transmitted through sneezing or coughing, contaminated food and water, or eating or sharing food with chronic HBV patients. The stigma and pattern of knowledge deficits observed in this study regarding HBV was similar to a previous study among adult residents in Ho Chi Minh city in which 55% had the mistaken impression that HBV can be spread by sharing eating utensils and 61% felt that persons with chronic HBV infection put others at risk [14]. It is widely recognized that HBV related stigma can negatively affect health behaviors related to screening, preventive, diagnostic and treatment for HBV infection [15].…”
Section: Discussionsupporting
confidence: 81%
“…A total of 17 articles quantitatively examined HBVrelated stigma. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and a further six articles provided a qualitative assessment of stigma, typically through either semi-structured interviews or focus group discussions. [35][36][37][38][39][40] The quantitative studies included a total of 15 studies conducted in people living with HBVor in the general population about people living with HBV and two studies that were conducted exclusively in healthcare providers.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…For example, Cotler et al (2012) 20 constructed the HBV Stigma Instrument, which was developed utilizing previously published surveys of stigma in HIV 41,42 and was subsequently used in two other studies identified in the current review. 21,23 A further two studies, both conducted in China, used the same five questions to assess HBV-related stigma in rural adults or rural migrants to a major Chinese city. 24,32 These questions related to the extent that a person was willing to interact, or let their children interact with someone living with chronic HBV.…”
Section: Quantitative Assessment Of Hbv-related Stigmamentioning
confidence: 99%
See 1 more Smart Citation